(untitled) (Journal of Forensic Medicine & Toxicology, 2024)
Sports activities have been associated with injuries to the players. But few sports do also lead to injuries to innocent bystanders and non participants. Kite flying is among such sport which injures both the participant and the innocent by standers and by passers. The string;used for flying kites, known as manja can cause fatal injuries while it can lead to cuts on hands of participants and can be in form of falls, electrical injuries. This paper discusses a case of cut throat injury caused by manja and the preventive measures to minimize the chances of injuries associated with kite flying.